P53 overexpression in Ewing's sarcoma/primitive neuroectodermal tumour is an uncommon event. Issue 2 (April 1995) - Mangham, D C; Cannon, A; Li, X Q; Komiya, S; Gebhardt, M C; Springfield, D S; Rosenberg, A E; Mankin, H J
Abstract : Aim —To determine the presence of p53 overexpression in Ewing's sarcoma/primitive neuroectodermal tumours (ETs) and to assess whether p53 accumulation has any prognostic value. Methods —From a prospectively compiled database of 76 patients with ETs, suitable tumour tissue was available for 38. The monoclonal antibody pAb1801 was used to detect p53 nuclear protein overexpression. Results —Nuclear staining was detected in the tumours of three (8%) of the 38 patients. Where tumours stained positively, over 10% of the tumour nuclei were postively stained. All three patients whose tumours overexpressed p53 died and in a relatively short time compared with the patients who did not overexpress p53 (mean 3·7 months compared with a mean of 38·7 months in the p53 negative group). Conclusion —Overexpression of p53 in ETs is an uncommon event. Overexpression of p53 has repeatedly been shown to correlate closely with p53 point missense mutations and therefore this oncogenic event appears not to be of primary pathogenic importance in ETs. There is a tentative indication that those uncommon ETs in which p53 overexpression can be detected may be-have more aggressively.